The changing patterns of liver cancer in Saudi Arabia over a 22-year period - Alshehri, Bandar M. (International Journal of Research in Medical Sciences, 2020)
Background: Liver cancer is a major public health problem in the developing world. It is the sixth most common cancer in the developed world and the second leading cause of death among cancer patients, globally. This study evaluated the trends and geographical distributions of liver cancer in the Saudi Arabian population. Methods: A secondary data analysis was performed on liver cancer cases registered in the Saudi Cancer registry for the period 1994 to 2015. In all, 8,785 liver cancer cases were included in the analysis, all of them Saudi nationals. Results: There were significant decreases in the mean age-standardised rates of liver cancer over the study period. The incidence of liver cancer varied by region. A strong positive correlation was observed between liver cancer incidence and age. Hepatocellular carcinoma-NOS is the most common histopathology subtype among the Saudi population. Conclusions: The overall trend of the liver cancer age-standardised rate for males and females decreased among the Saudi population. This rate varies by region. Studying this variation in more detail will help improve public health policy, optimise distribution of resources and allocation of funding for research on prevention and diagnosis and direct awareness programs to the regions that are most in need.